(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The midst of Covid-19, Thailand has been hit with lock down on the department stores. The government announce lockdown along with the uncertain situations of the Covid-19 pandemic have caused both business and consumer change their shopping behavior. This situation has been affecting the urban lifestyle among consumers who enjoys going to department store. The objective of this study is to investigate the influencing factors that affect the consumer’s perception on visiting the department store. The statistical analysis on factor analysis was conducted with 400 questionnaires. The questionnaires focus on the decision on the decision of the consumer’s consumption during Covid-19. This study aims to investigate 4 factors which are services of the mall, consumers’ satisfactions, Modernization of the shopping malls, and public relations of the shopping mall. The results finding suggest that social media online has significant influent factor to the consumer’s perception on their decision of department store services.This research can assist business in adapting to the new uncertainty situation of pandemic.